2004
DOI: 10.1158/0008-5472.can-04-0447
|View full text |Cite
|
Sign up to set email alerts
|

PT-100, a Small Molecule Dipeptidyl Peptidase Inhibitor, Has Potent Antitumor Effects and Augments Antibody-Mediated Cytotoxicity via a Novel Immune Mechanism

Abstract: The amino boronic dipeptide, PT-100 (Val-boro-Pro), a dipeptidyl peptidase (DPP) inhibitor, has been shown to up-regulate gene expression of certain cytokines in hematopoietic tissue via a high-affinity interaction, which appears to involve fibroblast activation protein. Because fibroblast activation protein is also expressed in stroma of lymphoid tissue and tumors, the effect of PT-100 on tumor growth was studied in mice in vivo. PT-100 has no direct cytotoxic effect on tumors in vitro. Oral administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
162
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 49 publications
9
162
1
1
Order By: Relevance
“…25) that tumor invasion could be reduced by introducing an inhibitor that blocks secretion of proteinase by stromal cells (fibroblasts/myofibroblasts). Targeting FAP by developing more effective drugs based on proven anti-FAP compounds such as Sibrotuzumab (Kloft et al 2004) and PT-100 (Adams et al 2004) is one possible strategy. Of course, other pathways are also potential targets, such as those involved in attachment of cells to the ECM (Chen et al 2008), but it has also been shown that when integrins are reduced cells may adopt other modes of movement, such as swimming by shape changes (Renkawitz et al 2009;Renkawitz and Sixt 2010).…”
Section: Discussionmentioning
confidence: 99%
“…25) that tumor invasion could be reduced by introducing an inhibitor that blocks secretion of proteinase by stromal cells (fibroblasts/myofibroblasts). Targeting FAP by developing more effective drugs based on proven anti-FAP compounds such as Sibrotuzumab (Kloft et al 2004) and PT-100 (Adams et al 2004) is one possible strategy. Of course, other pathways are also potential targets, such as those involved in attachment of cells to the ECM (Chen et al 2008), but it has also been shown that when integrins are reduced cells may adopt other modes of movement, such as swimming by shape changes (Renkawitz et al 2009;Renkawitz and Sixt 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies revealed tumor growth inhibition in lymphoma, melanoma, mastocytoma, and fibrosarcoma xenograft models. 16 In phase I dose-escalation studies in healthy volunteers, Val-boroPro doses greater than 100-150 μg showed significant, sustained inhibition of DPP-IV, and Val-boroPro was tolerated at doses up to 1200 μg per day. 17,18 In a phase I trial of Val-boroPro in patients receiving myelosuppressive chemotherapy, the maximum tolerated dose was not reached up to 1200 μg per day, although orthostatic hypotension was observed at 800 μg per day.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, FAP's effect on collagen remains cloudy, as evidenced by results that appear to conflict [4;14]. Since clinical trials targeting FAP are proposed or underway to determine if neoplastic invasion of ECM can be slowed or halted [31][32][33], and given that neither gelatin or denatured collagen is a component of ECM, the actual effect of this enzyme on its alleged ECM substrate, i.e., collagen, is important to clarify. The difficulty of producing FAP uncontaminated by other trace membrane proteinases could complicate efforts to obtain definitive collagen cleavage data; however, new purification methods developed in our laboratory for the production of significant amounts of pure human plasmaderived APCE as well as human rFAP prompted us to examine the potential proteolytic effects of each enzyme toward purified types I, III and IV collagens as substrates.…”
Section: Introductionmentioning
confidence: 99%